(untitled) (Communication & Society, 2000)
The article describes the origins and development of research about children as receivers and consumers of television advertising. Firstly, it analyses the academic discourse about children and television, its main milestones and the evolution of its research agenda. Secondly, the paper focuses on the studies about television advertising and children, its relevant aspects and development. Finally, the work offers some conclusions which contribute to define the origins and evolution of the academic research on children advertising in television.